2004
DOI: 10.1128/iai.72.11.6711-6716.2004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Transcribed byActinobacillus pleuropneumoniaein Necrotic Porcine Lung Tissue by Using Selective Capture of Transcribed Sequences

Abstract: Genes expressed by Actinobacillus pleuropneumoniae in necrotic porcine lung tissue were identified by selective capture of transcribed sequences analysis. In total, 46 genes were identified, 20 of which have been previously reported to be associated with in vivo expression or virulence in A. pleuropneumoniae or in other organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
66
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 45 publications
2
66
0
Order By: Relevance
“…As we had shown in previous studies, genes containing putative HlyX binding motifs are expressed by A. pleuropneumoniae under the influence of bronchoalveolar lavage fluid from infected pigs, and deletion of these genes can cause attenuation of the organism (2,15). In addition, an analysis of genes expressed in necrotic porcine lung tissue revealed the expression of DMSO reductase and several other genes involved in anaerobic metabolism under these conditions (1). This repeated isolation of presumably HlyX-regulated genes led to the hypothesis that deletion of this global anaerobic regulator would inhibit colonization and/or persistence in A. pleuropneumoniae if it was indeed involved in the regulation of the genes we identified.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…As we had shown in previous studies, genes containing putative HlyX binding motifs are expressed by A. pleuropneumoniae under the influence of bronchoalveolar lavage fluid from infected pigs, and deletion of these genes can cause attenuation of the organism (2,15). In addition, an analysis of genes expressed in necrotic porcine lung tissue revealed the expression of DMSO reductase and several other genes involved in anaerobic metabolism under these conditions (1). This repeated isolation of presumably HlyX-regulated genes led to the hypothesis that deletion of this global anaerobic regulator would inhibit colonization and/or persistence in A. pleuropneumoniae if it was indeed involved in the regulation of the genes we identified.…”
Section: Discussionsupporting
confidence: 60%
“…We have shown previously that A. pleuropneumoniae genes upregulated under anaerobic conditions in culture are not only upregulated in sequestered necrotic lung tissue where anoxic conditions are to be expected (1) but also upon the supplementation of culture medium with bronchoalveolar lavage fluid from A. pleuropneumoniae-infected pigs, which mimics conditions as they occur on respiratory epithelium (1)(2)(3)15). Further, we have shown that isogenic mutants lacking aspartate ammonia lyase (aspartase) activity or both dimethyl sulfoxide (DMSO) reductase and aspartase activity were reduced in virulence and in their ability to persist on unaltered respiratory epithelium (2,15).…”
mentioning
confidence: 99%
“…However, other putative adhesins have also been described, such as type IV fimbriae expressed under specific conditions in different serotypes (63), a 60-kDa collagen-binding protein (14), a 55-kDa outer membrane protein (61), and an autotransporter protein (4).…”
mentioning
confidence: 99%
“…In this study, many genes involved in iron acquisition were shown to be upregulated, while genes involved mainly in energy metabolism were downregulated. In vivo studies based on selective capture of transcribed sequences, in vivo expression technology, or signature-tagged mutagenesis (3,4,22,31,53) have allowed the detection of adhesin and toxin genes and of genes involved in metabolism, stress, regulation, and transport.…”
mentioning
confidence: 99%
“…Selective capture of transcribed sequences (SCOTS) has been used to identify genes expressed in vivo by bacterial pathogens such as Mycobacterium (13,14), Salmonella (15)(16)(17), Actinobacillus (18), Helicobacter pylori (19), and avian pathogenic Escherichia coli (20). In this report, we demonstrate that SCOTS can be used to obtain high-quality transcript profiles from intracellular bacteria such as Typhi within human macrophages, and that the use of microarrays and SCOTS-cDNA hybridization provides an effective means to elucidate the global bacterial expression profile from infected host cells.…”
mentioning
confidence: 99%